Analisis Risiko Investasi Saham Tunggal Syariah dengan Value at Risk (VaR) Menggunakan Simulasi Monte Carlo - Afifah Humayrah; Devni Prima Sari (Journal of Mathematics UNP, 2023)
Investment is an activity to hold a number of funds with the aim of gaining future profits, one of which is by investing in the Islamic capital market. Islamic capital market instruments that can be used are shares. Stocks are known to have the characteristics of high risk and high return, not only bringing high profits but also carrying high risks. One of the measuring tools that can be used to measure risk is Value at Risk because it can estimate the maximum possible loss that can occur on a single asset at a certain level of confidence. The purpose of this study is to estimate the optimal risk obtained by using Value at Risk with Monte Carlo Simulation. The data used in this study is the closing price of shares of PT Telekomunikasi Indonesia, Tbk which is listed in the Jakarta Islamic Index (JII). Based on research using initial investment funds of 100,000,000.00, IDR the value of Value at Risk is -3,620,898.95 IDR at an error level of 1%, -2,709,707.70 IDR at an error level of 5% and -2.120.418.85 IDR at an error level of 10. %.